The Nansen Legacy: Scientific exploration and sustainable management beyond the ice edge - Reigstad, Marit; Eldevik, Tor; Gerland, Sebastian (The Nansen Legacy Report Series, 2021)
The scientific investigation of a rapidly changing northern environment leads to research questions of such intellectual, empirical and logistical complexity—and of such importance to the management of national resources and associated international obligations—that they can only be addressed properly through national and prioritized cooperation, with the highest scientific standards.